Margin Pemasaran Beras Di Desa Langagon Satu Kecamatan Bolaang Kabupaten Bolaang Mongondow - Dunggio, Muhammad Hasan Habi; Ngangi, Charles R.; Loho, Agnes E. (Sam Ratulangi University, 2023)
This study aims to analyze the marketing margin and efficiency of rice marketing channels and institutions in Langagon Satu Village, Bolaang Sub-district, Bolaang Mongondow Regency. This research was conducted from August to December 2023. The data used in this research are primary data and secondary data. The sampling technique in the study used Purposive Sampling and Snowball Sampling. The number of Farmer samples was 10 respondents, Mill 1, Collecting Traders 4 and Collecting Traders 8 respondents. This research uses questionnaires and interviews to describe the pattern of rice marketing channels in Langagon Village which are then described. The data analysis method used is the analysis of Marketing Margin, Farmer's Share and Marketing Efficiency. The results showed that there are 2 patterns of rice marketing channels in Langagon Satu Village, namely marketing channel I is Farmer - Mill - Retailer - Consumer and marketing channel II is Farmer - Mill - Gatherer - Retailer - Consumer. The lowest margin is in marketing channel I obtained at Rp2,875, Farmer's share of 74.7%, this is because the marketing channel only uses 2 intermediary marketing institutions, and the smallest percentage of marketing efficiency is in channel I which is 5.08%, this is because the costs incurred by marketing channel I are smaller than marketing channel II.